(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
This article explores the challenges and opportunities associated with Public-Private Partnerships (PPPs) in Uzbekistan, particularly in relation to sustainable development. It discusses the main obstacles in regulatory, financial, and expertise domains that affect PPP effectiveness and outlines the potential benefits such as improved infrastructure and alignment with Sustainable Development Goals (SDGs). The paper recommends strengthening regulatory frameworks, managing financial risks, building capacity, and fostering innovation to maximize the benefits of PPPs for Uzbekistan's sustainable development.